Attitudes towards disability in the educational field: a systematic review - Torres Ortiz, Karin (2023)
The objective of the research was to systematically analyze scientific studies that contemplate the construct of attitudes towards disability within the educational field, published in articles, national and international magazines. For this, a review of the literature associated with the study variable was carried out. The search covered the period August 2021 - July 2022 through reliable sources such as: Scopus, Redalyc, Sciencedirect, Scielo, Refseek, Sci - hub, World Wide Science. Regarding the inclusion criteria, articles that have attitudes towards people with disabilities or associated terms as a variable, that the articles are in English or Spanish, and during the period from 2006 to 2021 were considered. Those studies whose data were excluded. are not precise in reference to the methodology, and whose results lack validity and reliability. All the investigations were carried out within the educational field, pointing out as predisposing factors to generate positive attitudes towards disability: sex, in this case female; age; the degree of information that is had about the disability and previous contact. with people with disabilities.